2016
DOI: 10.1038/bonekey.2016.20
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic actions of curcumin in bone disorders

Abstract: Curcumin is the active component of turmeric extract derived from the Curcuma longa plant. In the last decade, curcumin has raised a considerable interest in medicine owing to its negligible toxicity and multiple therapeutic actions including anti-cancer, anti-inflammatory and anti-microbial activities. Among the various molecular targets of curcumin, some are involved in bone remodeling, which strongly suggests that curcumin can affect the skeletal system. The review sheds light on the current and potential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 69 publications
(79 reference statements)
0
29
0
Order By: Relevance
“…It has attracted a considerable interest in medicine due to its negligible toxicity and multiple therapeutic effects including anti-cancer, anti-inflammatory and anti-microbial activities (Rohanizadeh et al ., 2016). Based on preclinical and limited clinical trials, curcumin has shown to be a safe and potential therapeutic agent against diseases, such as inflammatory bowel disease, pancreatitis, arthritis and chronic anterior uveitis, as well as certain types of cancers (Kunnumakkara et al ., 2008; Rohanizadeh et al ., 2016; Shehzad et al ., 2011). Studies, covering a treatment period of three months, have shown that curcumin does not possess acute toxicity at doses of 2 g/kg of body weight in mice and 8,000 mg/day in humans (Chainani-Wu, 2003; JS, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has attracted a considerable interest in medicine due to its negligible toxicity and multiple therapeutic effects including anti-cancer, anti-inflammatory and anti-microbial activities (Rohanizadeh et al ., 2016). Based on preclinical and limited clinical trials, curcumin has shown to be a safe and potential therapeutic agent against diseases, such as inflammatory bowel disease, pancreatitis, arthritis and chronic anterior uveitis, as well as certain types of cancers (Kunnumakkara et al ., 2008; Rohanizadeh et al ., 2016; Shehzad et al ., 2011). Studies, covering a treatment period of three months, have shown that curcumin does not possess acute toxicity at doses of 2 g/kg of body weight in mice and 8,000 mg/day in humans (Chainani-Wu, 2003; JS, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Curcumin has shown bone anabolic properties, but lacks bone specificity. 28 Curcumin is hydrophobic, highly instable in vivo, and has poor bioavailability. 29 Therefore, it could be used as a hydrophobic drug model to test the efficacy of bone-specific amphiphilic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin has not only anticancer but also bone anabolic properties. 28 Curcumin enhances bone-forming "osteoblast" differentiation, and the curcumin analog inhibits boneresorbing "osteoclast" formation. 49 Therefore, curcumin released from (Asp) 8 -PEG-PCL might kill the cancer cells metastasized in bone niche, as well as maintain bone homeostasis and inhibit osteolysis.…”
mentioning
confidence: 99%
“…To avoid such drawbacks, it is needed to utilize therapeutic agents with minimum side effects to normal organs. To address this need, scientists have investigated the use of a traditional medicine named curcumin in treatment of osteosarcoma . This can be administered for other cancer types like cervical cancer, colon cancer, lung cancer, pancreatic cancer, and breast cancer …”
Section: Introductionmentioning
confidence: 99%
“…Although curcumin demonstrates such benefits, its poor water solubility and fast degradation in physiological pH limit its effective practical usage. In fact, curcumin hydrophobicity disables its vascular and oral administration which results in poor absorption and reduced bioavailability after its administration . In order to overcome these problems, it is necessary to develop an adequate releasing formulations (hydrogels, liposome, dendrimer, micro/nano particles) for delivery of curcumin which has been explored for long time .…”
Section: Introductionmentioning
confidence: 99%